PERAN KELOMPOK BELAJAR (POKJAR) DALAM MENINGKATKAN EFIKASI DIRI GURU-GURU SD - Alpusari, Mahmud; Putra, Riki Apriyandi (Jurnal Pendidikan Guru, 2017)
This study aims to see the role of learning groups (POKJAR) in improving self-efficacy of elementary school teachers. Subjects were students (teacher / participants) POKJAR by the number of sampled as many as 171 people, who came from 5 POKJAR (Pakning, Air Molek, Sedinginan, Duri, and Chart). Selection of sample based on purposive random sampling. To obtain relevant data, the instruments used in this study are questionnaires and interview guidelines, which are arranged based on 4 indicators. The results showed that the self efficacy of teachers / participants in general showed good results. And there are 3 aspects that have the highest response or positive response (100%). Specifically, it asserts that the three aspects of teacher / participants to seriously follow the learning, felt confident of being able to follow the teaching in POKJAR because it can improve cognitive ability, confident that it can complete the task on time, and to resolve the matter of lectures and family issues wisely.